Al-Mukhtaṣar min Kitāb al-siyāq li-tārīkh-i Nīsābūr - al-Fārisī, ʿAbd al-Ghāfir, (Miras Maktoob, ISBN: 9789004365452., 2019)
In the Islamic middle ages, urban histories were for the most part not the kind of chronicle that one might think, covering the political, economic, or cultural history of a particular city over a certain time. Instead, they were a kind of 'who's who' directory of names of a city's prominent inhabitants, mostly from as far back as information would be available until the lifetime of the author. In the case of the city of Nishapur, which saw its greatest blossoming between the ninth and thirteenth centuries, there is al-Ḥākim al-Nīshāpūrī's (d. 405/1014) foundational Taʾrīkh Nīsābūr , an Arabic work-now lost-on which many later biographers relied. Al-Ḥākim's work was continued by ʿAbd al-Ghāfir al-Fārisī (d. 529/1134) in his al-Siyāq li-Taʾrīkh Nīsābūr . The text published here is described as a partial summary of al-Fārisī's work, although Frye in his The Histories of Nishapur (p. 10) still regarded it as a fragment of the Siyāq itself.